Experimental Study of Geotextile Effect on Bearing Strength and Permeability of Sudanese Cohesive Soils - M. E. Zumrawi, Magdi; I. A. Abdalgadir, Eslam (University of Khartoum Engineering Journal, 2022)
This paper focuses on the influences of geotextile on bearing strength and permeability properties of cohesive soils. Experimental investigation was conducted on three soils reinforced with geotextile sheets in one or more layers. The soil samples are compacted at optimum moisture content and maximum dry density in five layers with or without geotextile sheets. The California Bearing Ratio (CBR) and the permeability tests have been carried out on natural soils and soils with geotextile sheets. The experiments results have showed a significant decrease in the CBR and the permeability values of the three soils with the inclusion of geotextile sheets. The CBR values of geotextile reinforced soils have decreased by 70% for 4 layers of geotextile sheets. Also, the average reduction in the permeability of the three soils reinforced with 1-layer geotextile sheet is about 60% of the natural soils. Hence, it is concluded that provision of geotextile sheet with an activator such as lime or fly ash to increase the soil strength will be beneficial and economical option in earth dams and canal banks.